1992
DOI: 10.1111/j.1365-2044.1992.tb03248.x
|View full text |Cite
|
Sign up to set email alerts
|

Regurgitation and oesophageal rupture with cricoid pressure: a cActaver study

Abstract: SummaryThe efficacy of cricoid pressure was studied in 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0
6

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(95 citation statements)
references
References 13 publications
0
89
0
6
Order By: Relevance
“…In the UK, it is generally accepted that a force of 20 N should be applied to the cricoid cartilage in the awake patient [2], increasing to at least 30 N with loss of consciousness to prevent regurgitation [2,8,9]; laryngoscopic view and airway patency are best maintained if cricoid force is kept below 44 N [2,9]. The application of cricoid force has therefore become central to techniques that aim to reduce the risk of regurgitation and subsequent inhalation associated with obstetric and emergency anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the UK, it is generally accepted that a force of 20 N should be applied to the cricoid cartilage in the awake patient [2], increasing to at least 30 N with loss of consciousness to prevent regurgitation [2,8,9]; laryngoscopic view and airway patency are best maintained if cricoid force is kept below 44 N [2,9]. The application of cricoid force has therefore become central to techniques that aim to reduce the risk of regurgitation and subsequent inhalation associated with obstetric and emergency anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Cricoid force may be inadequately or incorrectly applied, with subsequent morbidity and mortality [4], even among trained personnel [5,6]. There is debate about the optimal cricoid force required during induction of anaesthesia [2,[7][8][9][10], but it has been demonstrated that accurate, sustainable force can be delivered by using a cricoid yoke, even after minimal operator training [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Cricoid pressure may be responsible for airway obstruction; a previous study has shown that cricoid pressure, with an unmeasured force, can cause airway obstruction in Ϸ 10% of cases [4]. A force of Ϸ 44 N was applied to the cricoid cartilage in that study, although a force of 30 N is adequate to prevent regurgitation [5]. A new technique has been described whereby cricoid pressure is applied in an upward and backward direction to improve the view at laryngoscopy [6] but it is not known whether this causes airway obstruction.…”
mentioning
confidence: 90%
“…It involves the application of backward pressure on the cricoid cartilage with a force of between 30 and 40 N [1][2][3][4][5] in order to occlude the upper oesophagus (although latterly it has been suggested that a force of 20-30 N [6][7][8] might be more appropriate). Failure to secure the airway in this way may put the patient at risk of developing aspiration pneumonitis, bacterial pneumonia and or bronchial blockage [9].…”
Section: Introductionmentioning
confidence: 99%